DZIELIMY SIĘ DOŚWIADCZENIEMApplication of TachoSil®dressing in treatment of penetrating heart injury - Sobczyński, Robert; Węgrzyn, Piotr; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
A 51-year-old man presented with a penetrating heart wound as a result of a suicide attempt with the use of a sharp tool (a knife). The knife moved into the chest, piercing the pericardium, and damaged the right ventricle of the heart. The surgical intervention was provided immediately. The penetrating heart wound was successfully corrected with TachoSil ® . The patient after six days of hospitalization was discharged from hospital in good condition.